Role of Respiratory Nitrate Reductase in Ability of Pseudomonas fluorescens YT101 To Colonize the Rhizosphere of Maize - Ghiglione, Jean-François (American Society for Microbiology, 2000)
Selection of the denitrifying community by plant roots (i.e., increase in the denitrifier/total heterotroph ratio in the rhizosphere) has been reported by several authors. However, very few studies to evaluate the role of the denitrifying function itself in the selection of microorganisms in the rhizosphere have been performed. In the present study, we compared the rhizosphere survival of the denitrifying Pseudomonas fluorescens YT101 strain with that of its isogenic mutant deficient in the ability to synthesize the respiratory nitrate reductase, coinoculated in nonplanted or planted soil. We demonstrated that under nonlimiting nitrate conditions, the denitrifying wild-type strain had an advantage in the ability to colonize the rhizosphere of maize. Investigations of the effect of the inoculum characteristics (density of the total inoculum and relative proportions of mutant and wild-type strains) on the outcome of the selection demonstrated that the selective effect of the plant was expressed only during the phase of bacterial multiplication and that the intensity of selection was dependent on the magnitude of this phase. Moreover, application of the de Wit replacement series technique to our results suggests that the advantage of the wild-type strain was maximal when the ratio between the two strains in the inoculum was close to 1:1. This work constitutes the first direct demonstration that the presence of a functional structural gene encoding the respiratory nitrate reductase confers higher rhizosphere competence to a microorganism.